Raising Dairy Herd Replacements - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 2001)
This publication discusses the decision making factors for raising dairy herd replacements.
MF399_2001_10
Keywords: MF399; Economics; Livestock; MF